Du vin vieux dans de nouvelles outres? Réflexions sur la proposition de règlement 'Dublin IV' - Daniela Vitiello (European Papers, 2016)
(Series Information) European Papers - A Journal on Law and Integration, 2016 1(3), 1235-1251 | European Forum Insight of 27 December 2016 | (Table of Contents) I. Introduction. - II. Les objectifs de la réforme et les instruments de sa réalisation. - III. Nœuds critiques en matière d'accès à la protection internationale et de traitement des demandeurs. - IV. Nœuds critiques par rapport à la coopération interétatique en matière d'asile. - V. Conclusions. | (Abstract) The forced migration upsurge in 2015 prompted the recast of the Common European Asylum System (CEAS), intended to bring "more Europe" into the integrated management of the Area of Freedom, Security and Justice. This achievement is deemed to be fundamental by EU institutions, in order to cope with emerging centrifugal forces and to ensure the security of European citizens. However, the tools proposed to reach these goals do not seem to match adequately the challenges raised by the mass influx of third country nationals seeking international protection in Europe. The last proposal for the recast of the Dublin III Regulation offers a clear instance of this hiatus, highlighting the legal and political flaws in the Union's strategic vision, concerning both the treatment of protection seekers and the efficiency and equity of responsibility-sharing mechanisms. Its adoption risks leading to the gradual disavowal of the legal premises of the CEAS and the proliferation of inconsistencies between EU action and its underpinning values. Vice versa, a more balanced solution could be imagined only relaunching convincingly the European project as a process of integration based on "concrete achievements which first create a de facto solidarity".